2015
DOI: 10.1002/mame.201500226
|View full text |Cite
|
Sign up to set email alerts
|

High Strength Self‐Healing Magnetic Elastomers With Shape Memory Effect

Abstract: Development of self-healing and shape memory elastomers is important for artificial smart materials. Here, a novel shape memory magnetic elastomer with high mechanical strength consisting of conventional polymer and Fe 3 O 4 nanoparticles is reported. The elastomer exhibit superparamagnetism, and superior selfhealing performance at elevated temperature. The tensile strength of the healed elastomer can be up to 12.0 MPa, and almost equal to that of virginal sample. These materials are capable of remote controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…The FTIR spectra of pure Fe 3 O 4 NPs (a) and Fe 3 O 4 @NVP‐DVB NPs (b, c) in Figure A were tested to measure the bonding on the surface of the pure Fe 3 O 4 NPs in Fe 3 O 4 @NVP‐DVB NPs. The blue rectangle area shows the characteristic absorption peak of Fe−O bond at about 580 cm −1 . The two grey rectangle areas whose peaks range from 750 cm −1 to 900 cm −1 and 1350 cm −1 to 1550 cm −1 are corresponded to the unsaturation C−H bending vibration of benzene ring and the C=C stretching vibration of benzene ring .…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The FTIR spectra of pure Fe 3 O 4 NPs (a) and Fe 3 O 4 @NVP‐DVB NPs (b, c) in Figure A were tested to measure the bonding on the surface of the pure Fe 3 O 4 NPs in Fe 3 O 4 @NVP‐DVB NPs. The blue rectangle area shows the characteristic absorption peak of Fe−O bond at about 580 cm −1 . The two grey rectangle areas whose peaks range from 750 cm −1 to 900 cm −1 and 1350 cm −1 to 1550 cm −1 are corresponded to the unsaturation C−H bending vibration of benzene ring and the C=C stretching vibration of benzene ring .…”
Section: Resultsmentioning
confidence: 89%
“…The blue rectangle area shows the characteristic absorption peak of FeÀ O bond at about 580 cm À 1 . [32] The two grey rectangle areas whose peaks range from 750 cm À 1 to 900 cm À 1 and 1350 cm À 1 to 1550 cm À 1 are corresponded to the unsaturation CÀ H bending vibration of benzene ring and the C=C stretching vibration of benzene ring. [47] The peak from 1000 cm À 1 to 1100 cm À 1 in the green rectangle area are related to the characteristic absorption peak of SiÀ O bond which represents the KH570 molecule embellished on the pure Fe 3 O 4 NPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[72] Exposing OMF at the targeted damage location will generate a high local magnetic heating that activates the nanoparticles and enhances the damage expansion at crack edges and accelerate the narrowing of macroscopic cracks. [299][300][301][302] As the polymer melt drives progressively into the damaged region, the nanoparticles keep migrating toward the edge of the crack because of the entropic depletion attraction. [300] Yang et al observed no obvious geometrical change when a millimeter cut in the polymer sample (0.23 vol% nanoparticles) was triggered by a 60 min magnetic field treatment.…”
Section: Self-healing and Self-testingmentioning
confidence: 99%
“…nitinol alloy), SMPs have attracted tremendous interest due to their dramatically larger recovery strain (up to 800 per cent vs less than 8 per cent), light weight, low cost, good processability and biocompatibility (Behl et al , 2010a; Yakacki and Gall, 2009; Xie, 2011; Habault et al , 2013; Hager et al , 2015). They have been extensively explored for a wide application, for example, heat-shrinkable tubes, reconfigurable morphing wings (Felton et al , 2013; Yakacki, 2013), smart textiles (Leng et al , 2009), sensors and actuators (Sun et al , 2014a, 2014b; Li and Serpe, 2016), self-healing materials (Wang et al , 2012a; Feng et al , 2016), surgical stents and sutures (Lendlein and Langer, 2002; Huang et al , 2013; Jing et al , 2016), deployable structures (Santo et al , 2012; Liu et al , 2014a) and implants for minimally invasive surgery (Yakacki et al , 2007; Liu et al , 2014b). Traditional thermo-responsive shape-memory effect (SME) is usually achieved in the process called “programming”, which makes the material retain a temporary shape for a long period at ambient conditions (Lendlein and Kelch, 2002).…”
Section: Introductionmentioning
confidence: 99%